Avalanche multiplication of charge carriers in nanostructured porous silicon - Timokhov, D.F.; Timokhov, F.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The phenomenon of avalanche multiplication of charge carriers in Al/PS-(c-Si) sandwich-structures based on nanostructured porous silicon (PS) is studied. Experimentally received dependences of ionization rates on intensity of an electrical field correspond to the diffusion mechanism of electron-hole pairs heating up to a threshold of ionization. The distinction of effective factors of shock ionization for electrons and holes is unsignificant. The estimation of length of free run of hot electrons is carried out at scattering of energy on the optical phonons.